Enhancing Students’ Mathematical Problem-Solving Skills through Problem-Based Learning in Systems of Linear Equations in Two Variables at Junior High School Level - Indriyati, Mia; Rodliyah, Iesyah (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study investigated the effect of Problem-Based Learning (PBL) on students’ mathematical problem-solving skills in Systems of Linear Equations in Two Variables (SPLDV), a contextual algebra topic that has received limited empirical attention in Indonesian junior high schools. Using a posttest-only control group design, the study involved 63 Grade VIII students of State Junior High School 2 Ngoro. The experimental group learned through PBL, while the control group received conventional instruction. The experimental group achieved a significantly higher posttest mean (78.12) than the control group (p < 0.05). The effect size (Hedges’ g = 1.14) indicated a very high effect, suggesting that PBL is particularly effective for improving students’ problem-solving skills in contextual SPLDV learning.